The risk of elevated plasma fibrinogen level in hypertensive and normotensive patientsafter bevacizumabintravitreal injection in diabetic retinopathy - Ni Luh Putu Widhyasti; Anik Ika Winarni; Natalia Christina Angsana; Rizto Wisuda Senuari; Angela Nurini Agni; Agus Supartoto; Suhardjo Prawiroranu; Tri Wahyu Widayanti; Tatang Talka Gani; Usi Sukorini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Bevacizumab intravitreal injection (IVB) could be detected in plasma that might cause an imbalance in the coagulation system. A hypercoagulable state is potentially involved in the risk for thrombosis, which is associated with high cardiovascular mortality.The objective of the current study was to investigate the risk of elevated plasma fibrinogen levelsin hypertensive and normotensive patients after IVB in diabetic retinopathy. This study was conducted at Dr. Sardjito General Hospital, Yogyakarta from March to June 2019. A total of 64 patients were enrolled in the study, included of 32 hypertensive and 32 non-hypertensive patients with diabetic retinopathy who underwent IVB. Patients were interviewed and investigated for physical condition and opthalmological examination. Fibrinogen levelwas measured before and 1 week after IVB. The mean fibrinogen level beforeand after IVB was slightly high in hypertensive patients than normotensive but not significantly different(p>0.05). There was no significant risk of increased fibrinogen levels after IVB in the hypertension group compared to the normotension group in diabetic retinopathy patients. The proportion of patients at high risk for cardiovascular disease after IVB was not significantly different between both groups.